Kontinuirna peč za žarjenje valjanih profilov v zaščitni atmosferi - Lipuš, Alain (Kovine zlitine tehnologije, 1998)
New continuous annealing furnace in bar mill is designed for heat treatment of high quality alloy steels. The furnace is totally computer controlled and enables immediate visual control of all important parameters of the heat treatment. Besides that it is also far more productive and consumes less energy than similar older furnaces. Controlled atmosphere is based on nitrogen. The most important fact is that we don't have additional decarburisation after heat treatment, which effects the quality of rolled bars very negatively.
Keywords: jeklarstvo; peči; toplotna obdelava; žarjenje